دراسة تأثير الداء السكري نمط II على وظائف الرئة - حجازية, مالك; سلمان, ربا; كنيفاتي, آية (Latakia University Journal -Medical Sciences Series, 2018)
مقدمة : الداء السكري هو مشكلة صحيّة عامّة كبرى و هنالك ازدياد مستمر في معدل الوقوع والاختلاطات طويلة الأمد . هذه الاختلاطات هي بشكل رئيسي عقابيل للتخرب الوعائي المجهري في الأعضاء الهدفية . إن حدوث العديد من الأذيات الرئوية في سياق الداء السكري نظراً لوجود دوران مجهري غزير و وفرة في النسج الضامة , يرفع احتمال أن يكون النسيج الرئوي عضواً هدفياً عند مرضى الداء السكري .أهداف البحث : صمم هذا البحث لدراسة تأثير الداء السكري و كل من مدة الإصابة بهذا المرض و ضبط الحالة السكرية على وظائف الرئة .المواد و الطرق : دراسة مقطعية – عرضية , أجريت على 75 من مرضى الداء السكري نمط II من مراجعي مشفى تشرين الجامعي في الفترة الممتدة بين تشرين أول 2015 حتى تشرين أول 2016. و تمت المقارنة مع مجموعة شاهد تألفت من 75 فرداً سليماً غير مصاب بالداء السكري . تم إجراء قياس للخضاب الغلوكوزي , سكر الدم الصيامي و إجراء اختبار وظائف رئة (spirometry) لجميع المشاركين في الدراسة و تم تسجيل القياسات الرئوية التالية : الحجم الزفيري الأقصى في الثانية الأولى (FEV1) , السعة الحيوية القسرية (FVC) , النسبة (FEV1/FVC) . تم تحليل النتائج باستخدام : المتوسط ± الانحراف المعياري , كاي مربع لبيرسون , معامل ارتباط بيرسون , و اختبار ANOVA .النتائج : إن متوسط النسبة المئوية من FEV1 المتوقعة و FVC المتوقعة عند المصابين بالداء السكري نمط II أقل مقارنةً بالاصحّاء غير السكريين (الحالات الشاهد) (P<0.05) . و إن هذه القيم كانت أخفض عند المرضى غير مضبوطي سكر الدم مقارنةً بالمرضى مضبوطي سكر الدم , و كذلك كانت القيم أخفض عند المرضى المصابين لفترة زمنية أطول بالداء السكري نمط II . الخلاصة : تقترح الموجودات في هذه الدراسة أن الرئة هي عضو هدفي لإصابة الداء السكري . و أن المرضى السكريين لديهم تراجع في وظائف الرئة مقارنةً بغير السكريين بنوذجٍ آفة حاصرة و تتدهور وظائف الرئة كلما طالت مدة الإصابة بالداء السكري و كلما كان السكري غير مضبوطٍ .Background: Diabetes mellitus is a leading public health problem with increasing incidence and long term complications. These complications are mainly a consequence of macro-vascular and microvascular damages of the target organs. The incidence of several pulmonary abnormalities during the course of Diabetes Mellitus because the presence of an extensive microvascular circulation and abundant connective tissue in the lungs , raises the possibility that lung tissue may be a target organ in diabetic patients.Objectives: This research is designed to study the impact of DM and both the duration of the disease and the glycemic control on pulmonary function tests.Methodology: This is a cross-sectional study carried out on 75 patients with type II diabetes mellitus patients at Tishreen University Hospital in the period between October 2015 and October 2016 .We compared with a control group consisted of 75 non diabetic healthy persons . Measurement of HbA1C , fasting plasma glucose (FPG) , and spirometry were made to all subjects and the following pulmonary function parameters were recorded: Forced Expiratory Volume in the first second (FEV1), Forced Vital Capacity (FVC), and Forced Expiratory Volume percent (FEV1/ FVC%) . Results were analyzed by calculating Mean ± SD, using X2 test , Karl Pearson correlation and ANOVA test.Results: The mean FEV1, FVC, FEV1/FVC% values were low in diabetics (p value <0.05) compared to healthy non-diabetics (control group). Also, uncontrolled diabetics show a greater decrease in these values than controlled diabetics. There was a greater decrease in these values in patients with long period of disease . Conclusion: The findings of the present study suggest that, the lung is a target organ for damage in DM and diabetics show a decrease in PFTs with a restrictive pattern lesion compared with non-diabetics . And this deterioration is exaggerated in uncontrolled diabetics and with the long duration of DM .